EFQM Model and an Autonomous organization linked to a local entity. Is there compatibility? - Ruiz Moreno, Antonia; Cuerva Sellés, Victoria; Cabeza Pulles, Dainelis; Roldán Bravo, María I. (Cuadernos de Estudios Empresariales, 2017)
The quality is recognized today as one of the business techniques that enable organizations to improve their management processes and be competitive. That is why, this research aims to make an empirical analysis on an assessment of the quality of an autonomous body of a local entity supported by the EFQM business excellence model. To test the hypothesis, a single questionnaire per sample unit and enough units and for statistical analysis Descriptive statistical analysis was used. Our study provides information on management in public organizations and their links with quality management. Some conclusions, limitations, future research and practical implications of the analysis are presented.